One watercolor a day : a 6-week course exploring creativity using watercolor, pattern, and design - Lawlor, Veronica (One a Day Ser., 2013)
Spark new ideas and increase your creativity with One Watercolor a Day. This enchanting art book contains six weeks worth of daily watercolor paintings and exercises to help you cultivate your imagination and develop your style. Each day will bring you a new painting by one of eight professional illustrators and includes a description of the work, helpful comments by the artist, and a companion exercise that encourages you to put brush to paper to create your own works of art. Uncover new techniques and solutions, and get valuable advice on how to approach and execute your own artwork. Professional tips throughout the book will broaden your knowledge on watercolor painting. One Watercolor a Day brings the world of watercolor painting to your paintbrush and is sure to become a motivational and inspirational book in your personal library.